พื้นที่ขั้นต่ำของการนั่งท่าขัดสมาธิสำหรับผู้สูงอายุไทย - ไพโรจน์ ลดาวิจิตรกุล (ภาควิชาวิศวกรรมอุตสาหการและการจัดการ คณะวิศวกรรมศาสตร์และเทคโนโลยีอุตสาหกรรม มหาวิทยาลัยศิลปากร, 2022)
Cross-legged sitting requires the movement more complex than the normal sitting on the chair which is hard to balance while getting up and sitting down and need a large space for balancing. In a small place or crowded area, Cross-legged sitting in the small space of elder may cause the fall or hit accidents then the space of Cross-legged sitting is important to control the number of people suiting for the space. Based on the body movement data in 3 Dimensions of 50 active elders with average age at 66 years old. The space of Cross-legged sitting during sit down and stand up (Dynamic measurement) has the width at 134.4 cm. and the depth at 131.5 cm. at 95 percentiles. Comparing to the space of still sitting (Static measurement), it showed that the width is 2.2 times and the depth is 1.7 times of the still sitting. In order to make it easy to use and remember, the space of Cross-legged sitting for public area covering both male and female should be 1.8 Sq.m. (1.35×1.35 m.)